2020
DOI: 10.1097/inf.0000000000002826
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization in South African Adolescents With Perinatally Acquired HIV on Antiretroviral Therapy

Abstract: Background-Little is known about hospitalization in African adolescents with perinatally acquired HIV (PHIV+ adolescents). We described the incidence and causes of hospitalization in participants enrolled in the Cape Town Adolescent Antiretroviral Cohort in South Africa.Methods: Data collected from July 2013 through October 2018 from PHIV+ and HIV− adolescents were analyzed. Participants were assessed every six months and data on intercurrent hospitalization were abstracted. Causes of hospitalizations were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Hospitalization was higher in males than females and significantly shifted to adolescents, with a 5-fold higher risk in those older than 15 years. Conversely, Frigati et al 19 found no association between hospitalization and sex. They found that older adolescents had a lower incidence rate of hospitalization than younger adolescents in South African adolescents.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Hospitalization was higher in males than females and significantly shifted to adolescents, with a 5-fold higher risk in those older than 15 years. Conversely, Frigati et al 19 found no association between hospitalization and sex. They found that older adolescents had a lower incidence rate of hospitalization than younger adolescents in South African adolescents.…”
Section: Discussionmentioning
confidence: 94%
“…While hospitalization among adolescents may indicate poorer treatment adherence and increased AIDS-related morbidity, it also includes non-AIDS-related admissions like violence exposure, traffic accidents, mental health issues and pregnancies, highlighting the need to strengthen adolescent care holistically. 19 In South Africa, young boys and men have a 3-fold higher level of violence exposure than girls. 20 While we did not have data on admission reasons, Dicko et al 18 reported that 62% of hospitalizations in children with HIV in West Africa were AIDS-related.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, one of the reasons for hospitalization among adolescents and young people can be related to untreated HIV/AIDS, which consequently increases the cases of repeated infections. The age group between 10 and 24 has the highest follow-up loss rates and worst virological results (40). It is essential to highlight that, in addition to demographic and clinical factors, socioeconomic disadvantages, social circumstances, mental health disorders and adverse lifestyles are also factors for hospitalization (41).…”
Section: Discussionmentioning
confidence: 99%
“…Despite improvements in morbidity and mortality of children with HIV [13,14], frequency of hospital admissions and mortality during hospitalizations remain a concern [15][16][17][18]. Existing literature mostly describes hospitalization patterns among older children [19][20][21][22], tends to focus largely on cause-specific hospitalizations [23,24], and assesses time periods before the introduction of universal ART access [25][26][27]. This study aims to describe hospitalization patterns and examine factors associated with hospitalization among infants with HIV in the era of universal birth testing and universal ART in South Africa.…”
Section: Introductionmentioning
confidence: 99%